Kajian Hukum Islam Terhadap Tradisi Kirim Dungo Sebelum Akad Nikah: Studi di Desa Wringinagung Jember - Nisa, Urfi Maslikhatun; Wulandari, Yunita (Maqasid: Jurnal Studi Hukum Islam, 2025)
Tradition is a series of activities that are inseparable from the life of the village community and continue to be preserved from generation to generation. One of the traditions that is still maintained is the tradition of sending dungo before the marriage contract, which is a joint prayer activity as a form of asking for blessings and safety for the family and the bride-to-be. This study aims to analyze the tradition of sending dungo in the perspective of Islamic law, especially in the concept of 'urf. This research uses a qualitative method with an ethnographic approach to understand the practice of this tradition in people's lives. The results of the study show that the tradition of sending dungo can be categorized as 'urf sahih, which is a tradition that does not contradict Islamic shlaw. This tradition has positive value as part of the prayer for blessing and salvation, but it has no status as an obligation in a marriage. Therefore, in its implementation, it must remain in line with the principles of Islamic law without being considered an obligation in marriage.